A novel hybrid fuzzy pid controller for attitude stabilization of a remote operated quadrotor unmanned aerial vehicle - Zul Azfar Ahmam (School of Mechatronic Engineering, 2012)
This thesis presents a new attitude control development to be implemented in the flight control board (FCB) of quadrotor unmanned aerial vehicle (UAV). A simple structure of quadrotor was developed to test the attitude stabilization control.